2022
DOI: 10.1186/s12909-022-03623-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of video interviews for orthopaedic surgery residency during COVID-19

Abstract: Background During the 2020–21 residency interview season, interviews were conducted through virtual platforms due to the COVID-19 pandemic. The purpose of this study is to assess the general perceptions of applicants, residents and attendings at a single, large, metropolitan orthopaedic residency with regards to the video interview process before and after the interview season. Methods Surveys were sent to all orthopaedic applicants, residents, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Three additional studies, 2 that focused on fellowship applicants, also found that virtual interviews were more cost-effective for applicants 26-28 . That said, 2 studies found that most applicants preferred in-person interviews to virtual ones 19,29 . However, regarding fellowship interviews, a study of pediatric orthopaedic fellowship applicants found that 67% did not feel that the virtual interview format negatively affected the process, and nearly half (48.5%) preferred to keep fellowship interviews virtual in the future 24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three additional studies, 2 that focused on fellowship applicants, also found that virtual interviews were more cost-effective for applicants 26-28 . That said, 2 studies found that most applicants preferred in-person interviews to virtual ones 19,29 . However, regarding fellowship interviews, a study of pediatric orthopaedic fellowship applicants found that 67% did not feel that the virtual interview format negatively affected the process, and nearly half (48.5%) preferred to keep fellowship interviews virtual in the future 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Program directors (PDs) placed more weight on communication from faculty mentors, emails from applicants, home applicant status, and virtual information session attendance 31 , whereas less importance was given to virtual away rotations and virtual interviews 30 , 32 . PDs and faculty generally preferred in-person interviews 19 , 26 , 29 , given the perceived inability to assess candidate fit, social, interpersonal, clinical, and surgical skills; commitment; and genuine interest through the virtual format 25 , 26 . However, some programs continued to place significant weight on faculty and resident interviews, although they were virtual 19 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these sentiments have been echoed in other articles, with both applicants and program directors reporting diminished ability to adequately assess applicant quality and program compatibility, respectively, following virtual interviews compared to in-person interviews. 3,4 Applying to orthopaedic surgery residencies requires diligent work in the face of increasingly fierce competition, complicated by the everchanging nuances in the application process. It is prudent to consider recent trends in the application process discussed in this article when deciding which residency programs to apply to to optimize one's chances of matching into this highly regarded specialty.…”
mentioning
confidence: 99%